Trajectory of hippocampal fibres to the contralateral anterior thalamus and mammillary bodies in rats, mice, and macaque monkeys. (August 2019) - Mathiasen, Mathias L.; Louch, Rebecca C.; Nelson, Andrew D.; Dillingham, Christopher M.; Aggleton, John P.
The routes by which the hippocampal formation projects bilaterally to the anterior thalamic nuclei and mammillary bodies were examined in the mouse, rat, and macaque monkey. Despite using different methods and different species, the principal pattern remained the same. For both target areas, the contralateral hippocampal (subiculum) projections arose via efferents in the postcommissural fornix ipsilateral to the tracer injection, which then crossed hemispheres both in or just prior to reaching the target site within the thalamus or hypothalamus. Precommissural fornix fibres could not be followed to the target areas. There was scant evidence that the ventral hippocampal commissure or decussating fornix fibres contribute to these crossed subiculum projections. Meanwhile, a small minority of postsubiculum projections in the mouse were seen to cross in the descending fornix at the level of the caudal septum to join the contralateral postcommissural fornix before reaching the anterior thalamus and lateral mammillary nucleus on that side. Although the rodent anterior thalamic nuclei also receive nonfornical inputs from the subiculum and postsubiculum via the ipsilateral internal capsule, few, if any, of these projections cross the midline. It was also apparent that nuclei within the head direction system (anterodorsal thalamic nucleus, laterodorsal thalamic nucleus, and lateral mammillary nucleus) receive far fewer crossed hippocampal inputs than the other anterior thalamic or mammillary nuclei. The present findings increase our understanding of the fornix and its component pathways while also informing disconnection analyses involving the hippocampal formation and diencephalon.